2022
DOI: 10.3390/app122211867
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study and Numerical Simulation of W/O Emulsion in Developing Heavy Oil Reservoirs

Abstract: In the process of waterflooding development of heavy oil, W/O emulsion has a strong ability to improve the mobility ratio and block the high-permeability layer, which can effectively improve the sweep coefficient and enhance oil recovery. In this paper, the stability and droplet size distribution of emulsions under different conditions were studied by taking heavy oil and formation water from Jimusar Oilfield in Xinjiang as samples. On this basis, double-pipe core flooding experiments were carried out to study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…The uncontrolled proliferation of renal mesangial cells is an important pathological feature of human renal diseases, including diabetic nephropathy (Cove-Smith & Hendry, 2008). In our study, we found that the proliferation of HRMCs was promoted under HG condition, which was consistent with the results of previous studies (Wang et al, 2022;Zhu et al, 2021). Hyperglycemia-induced oxidative stress has important roles in pathogenesis of diabetic nephropathy (Rosas-Martínez et al, 2021;Vodosek Hojs et al, 2020), and HG could result in oxidative stress in renal mesangial cells (Wan et al, 2022;Wei et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…The uncontrolled proliferation of renal mesangial cells is an important pathological feature of human renal diseases, including diabetic nephropathy (Cove-Smith & Hendry, 2008). In our study, we found that the proliferation of HRMCs was promoted under HG condition, which was consistent with the results of previous studies (Wang et al, 2022;Zhu et al, 2021). Hyperglycemia-induced oxidative stress has important roles in pathogenesis of diabetic nephropathy (Rosas-Martínez et al, 2021;Vodosek Hojs et al, 2020), and HG could result in oxidative stress in renal mesangial cells (Wan et al, 2022;Wei et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…The ISC technology utilizes underground chemical reactions to thermally decompose heavy oil into light oil, thereby improving the quality of the extracted oil. This process encompasses various displacement mechanisms, including heating and viscosity reduction, chemical modification, steam distillation, non-miscible gas displacement, and carbon dioxide miscible displacement [15,16]. ISC technology consumes only about 20% of the fuel compared to other methods, effectively displacing the remaining oil and leading to a theoretical recovery rate exceeding 70%.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, numerous researchers have employed laboratory experiments and numerical simulations to investigate the flow patterns in tight oil and gas reservoirs. Laboratory experiments focusing on flow characteristics generally use either steady-state or transient methods [4][5][6][7]. Ren et al [8] applied the steady-state method and capillary equilibrium technique to accurately delineate the seepage characteristics of tight oil.…”
Section: Introductionmentioning
confidence: 99%